Effect of Job Motivation and Organizational Commitment On Employee Satisfaction at PT Maju Mandiri Utama - Ronnie Resdianto Masman; Viny Angellika; Louis Utama (LPPM Universitas Buddhi Dharma, 2023)
This study aimed to determine the effect of work motivation on employee job satisfaction and the effect of organizational commitment on employee job satisfaction at PT Maju Mandiri Utama in Central Jakarta. Job satisfaction that comes from human resources who work in the company, then for this satisfaction employees will be more enthusiastic about doing the tasks that are their obligations. Job satisfaction is also related to work motivation, both owned by the employee self and motivation from the surrounding environment such as colleagues, superiors, or subordinatesWork motivation will increase employees to achieve their job satisfaction so that employees will be proud of the results they get and are encouraged to maintain and improve their performance. The sampling method illustrated in this research uses convenience sampling with 100 employees as respondents, 5 of whom were respondents in the initial survey of the study and 95 employees were respondents in the study. The Smart Pls3 analytical kit was used in this study. The results showed an influence of work motivation on the job satisfaction of PT Maju Mandiri Utama employees in Central Jakarta, and there was an influence of organizational commitment on the job satisfaction of PT Maju Mandiri Utama employees in Central Jakarta